Soulana Maria Valamoti, Plant foods of Greece. A culinary journey to the Neolithic and Bronze Ages. - Perlès , Catherine (Journal of Greek Archaeology, 2024)
This is a truly exceptional book: although based on the most rigorous scientific research, it reads like the best fiction or travel book and leads the reader from surprise to surprise. It is also written in a very literary, sometimes poetic styles, which constantly betrays not only the love of the author for plants, but even more for human beings, whether long dead or well-alive. The book has also been well served by the publisher, with an elegant layout, numerous colour pictures and a detailed index.